Analysis on Operation Performance of Power Market and Clean Energy Transactions in Northwest China - Ruifeng LIU; Xiaofang QI; Yuankang HE; Tian’en CHEN; Xuan LUO; Wen ZHANG (Zhongguo dianli)
Aiming at establishing an analytical system of transaction operation performance, covering power market forms, electricity space, market system and market range, this paper makes a multi-dimension statistical analysis of the power transaction operation data based on the power market construction and power transaction operation practices in northwest China. A study is conducted on the main categories of transaction demands of trans-region and trans-province market operations, so as to provide a reference for promoting the power market construction, new energy utilization, and transaction value creation in northwest China. In addition, this paper tries to describe the current overall features of power market transaction in northwest China, so as to provide a reference for market players to better participate in the power market transaction, determine the marketing strategy and make trading decisions. The focus of this paper is put on the trading types and trading mechanisms for improving the utilization level of renewable energy, and some suggestions are proposed to improve the operation quality of the power market.